"A Mountain of Words": Children's Literacy in Rural France, 1800–1950. Issue 3 (1st December 2019) - Macknight, Elizabeth C.
Abstract : This article presents an interdisciplinary approach to archival research on records produced by children that survive in family archives. It corresponds with the aims of education specialists who investigate patterns in language learning to understand how young minds absorb influences concurrently from familial, religious, and social circles across disparate cultural settings. Drawing upon the concept of syncretic literacy, the article interprets French archival evidence of children's development of linguistic competency and sensitivity to language use in context. It argues for the need to advocate both the conservation of children's archives and the design of educational programs that enable children to discover the role of archivists and the purposes of recordkeeping in society.